In vitro and In vivo Antioxidant, Anti-hyperlipidemic Properties and Chemical Characterization of Centella asiatica (L.) Extract - Kumari, Sima; Deori, Meetali; Elancheran, R.; Kotoky, Jibon; Devi, Rajlakshmi (Frontiers in Pharmacology, 2016)
The study aimed to identify the phenolic compounds present in Centella asiatica (L.) (C. asiatica) extract and evaluate the respective antioxidant potential as well as its cholesterol-lowering effects in the experimental animal model. Herein, the antioxidant potential of extracts was assessed by its free radical scavenging activity such as 2, 2-diphenyl -1- picrylhydrazyl as well as reducing capability. The antihyperlipidemic effects of C. asiatica extract (CAE) were evaluated in high cholesterol-fed (HCF) rats for 4 weeks, where different concentrations of extracts (0.25, 0.5 and 1 g/kg/day) were orally administrated daily. Lipid and antioxidant profiles, including total cholesterol (TC), triglyceride (TG), low- density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and superoxide dismutase (SOD), together with the indices of hepatic functions were also examined. C. asiatica revealed excellent free radical scavenging activity as revealed by DPPH assay, with the IC50 values (9.62 ± 0.88 μg/mL). Furthermore, C. asiatica extracts and fenofibrate remarkably lowered the level of TC, TG, LDL-C, and showed elevated levels of HDL-C, SOD. The histopathological observations further demonstrated clear differentiation and structural changes in liver of HCF and CAE treated group. Furthermore, gulonic acid, ferulic acid, kaempferol, chlorogenic acid, and asiatic acid were identified to be the major components which might be responsible for the antioxidant activity of the C. asiatica extract as evidenced from an ultra-high performance liquid chromatography–mass spectrometer (UHPLC-MS/MS). Taken together, these results signifies the excellent antioxidant and antihyperlipidemic properties of C. asiatica leaf extracts, which might be useful for the treatment of oxidative-stress related diseases such as hyperlipidemia.